Chromatic, photometric and thermal modeling of LED systems with nonidentical LED devices - Chen,HT; Lin,DY; Tan,SC; Hui,SYR (IEEE Transactions on Power Electronics, 2014)
With the emergence of new color-mixing LED systems based on LED devices of different color temperatures, the need for a new modeling technique for LED systems with nonidentical LED devices becomes imminent. This paper presents a modeling technique for LED systems with LED arrays comprising nonidentical LED devices that have nonidentical optical-thermal-electrical properties. Based on a general 3-D photo-electro-thermal LED node model, LED devices of different kinds can be arranged in various array forms according to their system construction and design. By linking the system matrix to the correlated-colorerature prediction, the proposed modeling technique provides an accurate prediction of the temperature distribution, luminous flux, and correlated color temperature of the LED systems. The temperature distribution and light output of the LED systems have been measured using an infrared imaging system and a spectrophotocolorimeter with an integrating sphere. The modeling technique has been successfully demonstrated and experimentally verified on several LED systems comprising nonidentical LED devices. It is particularly useful as a modeling tool to study new color-mixing LED systems based on different types of LED devices. © 2014 IEEE.